Bacterial attachment and biofilm formation on stainless steel surface and their in vitro inhibition by marine fungal extracts. Issue 3 (1st March 2018) - Mahyudin, Nor Ainy; Mat Daud, Noor Ifatul Hanim; Ab Rashid, Nor‐Khaizura Mahmud; Muhialdin, Belal J.; Saari, Nazamid; Noordin, Wan Norhana
Abstract: This study evaluates anti‐biofilm activity of four extracts from marine fungi; Penicillium citrinum PR1T4, Sarocladium strictum PP2L4, Aspergillus sydowii PR3T13, and Aspergillus spp. PR5T4 against Staphylococcus aureus, Listeria monocytogenes (ATCC 19115), Escherichia coli, and Salmonella typhi (ATCC 14028). The ability of bacterial cells to adhere, detach, and form biofilm on stainless steel surface were examined and ethyl acetate extract of the fungal culture (15 mg/ml) were tested for anti‐biofilm activity for 3, 6, 9, 12, and 15 days. E. coli showed the highest ability to adhere (>8 log CFU/cm 2 ) and lowest detachment (<4 log CFU/cm 2 ) after 24, 48, and 72 hr. Extract PP2L4 had the highest anti‐biofilm activity against S. typhi (1.70 ± 0.04 log CFU/cm 2 ). Fungal extracts, bacteria, and incubation period were significant factors and their interactions were significant. The results showed that marine fungal extracts are important natural sources for anti‐biofilm agents that have high potential as food‐contact surface sanitizers. Practical applications: Biofilm removal from food contact surfaces has been one of the greatest challenges for food industry. There have been efforts to explore natural agents with anti‐biofilm properties. This study showed that marine‐derived fungal extracts significantly reduced the number of attached cell on stainless steel discs and, therefore, is potential candidates for anti‐biofilm agents. Special attention would be given to the fungal isolate ( S. strictum PP2L4) that presented a promising activity against the gram‐negative S. typhi . As the active fungal extracts were unable to completely remove the adhered bacterial cells, optimization is recommended to increase probability of isolating active compounds capable for complete biofilm removal. The active compounds could be used in sanitizer formulation and applied on various food‐contact surfaces (e.g., stainless steel and plastic) at food related industries such as in institutional food service kitchens as well as home kitchens.